FACTORS INFLUENCING STUDENTS’ DECISIONS IN CHOOSING PRIVATE INSTITUTIONS OF HIGHER EDUCATION IN MALAYSIA: A STRUCTURAL EQUATION MODELING APPROACH - Osman M. Zain; Muhammad Tahir Jan2; Andy B. Ibrahim (Asian Academy of Management Journal, 2013)
There are almost 500 institutions of private higher education currently in operation in Malaysia which comprises colleges, university colleges, and fully university status. These institutions are helpful in filling the gap of the limited seats for potential students in government institutions of higher learning. A total sample of 373 students comprising students of from secondary schools were used in the study. These students are in the British equivalent O and A level of education. A questionnaire containing 46 statements was distributed randomly to the respondents during the motivation seminar at their respective schools. The data analysis was conducted using SPSS and AMOS software programme packages for windows. Factor analysis was performed to extract and decide on the number of factors underlying the measured variables of interest. Structural equation modelling (SEM) was then used to examine the variables and the fitness of proposed model. Results indicate a substantial positive effect of perception and promotion on the students’ choice of private institution for higher education. Results also reveal significant positive effect of perception on influence and promotion on influence. The findings of this study have a major implication for private institutions of higher education.